2013
DOI: 10.1542/peds.2013-1021q
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of a Cellular Phone-Enhanced Home Visitation Parenting Intervention

Abstract: BACKGROUND AND OBJECTIVES: Although home visiting programs have been documented to improve parenting in high-risk families, their effectiveness is diminished when parents disengage from programs. Cellular phones offer an approach to promoting parent engagement and enhancing parenting outcomes. Our objective was to examine whether mothers in a parenting intervention, Planned Activities Training (PAT), or cellular phone-enhanced version (CPAT) of the intervention would demonstrate greater use of parenting strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 16 publications
(14 reference statements)
0
66
0
2
Order By: Relevance
“…Hypotheses were based on the findings by Carta and colleagues (2013) which demonstrated positive changes in parent stress and parent-child interaction in mothers at-risk who participated in the SafeCare Parent-Child Interaction Module. As this is one of the first randomized trials examining an evidence-based, behavioral parenting program targeting child maltreatment prevention for fathers, many questions remain about how to most effectively serve this population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hypotheses were based on the findings by Carta and colleagues (2013) which demonstrated positive changes in parent stress and parent-child interaction in mothers at-risk who participated in the SafeCare Parent-Child Interaction Module. As this is one of the first randomized trials examining an evidence-based, behavioral parenting program targeting child maltreatment prevention for fathers, many questions remain about how to most effectively serve this population.…”
Section: Discussionmentioning
confidence: 99%
“…The program teaches a variety of skills focused on positive parenting, home safety, and child health. Studies examining SafeCare have revealed statistically significant reductions in child abuse perpetration and recidivism (Chaffin, Hecht, Bard, Silovsky, & Beasley, 2012; Gershater-Molko, Lutzker, & Wesch, 2002), as well as improved parenting skills among participants (Carta, Lefever, Bigelow, Borkowski, & Warren, 2013). While there have been no randomized research trials to date examining SafeCare with fathers, two pilot studies indicate that fathers exhibit positive improvement in target parenting skills in response to the SafeCare Parent-Child Interaction module (Bigelow & Lutzker, 1998; Self-Brown et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, SC was developed to reduce the occurrence of risk factors for child maltreatment by improving parent-child/infant relationships, parent knowledge and skills, and other contextual environmental factors (Lutzker & Bigelow, 2002). The efficacy of the SC model in reducing child maltreatment was demonstrated among multiple populations of at-risk parents, including parents referred from child protective services, substance abuse treatment programs, and agencies that serve disadvantaged families (Carta, Lefever, Bigelow, Borkowski, & Warren, 2013; Chaffin et al, 2012b; Silovsky et al, 2011). …”
Section: Introductionmentioning
confidence: 99%